KEMITRAAN KONSERVASI PEMULIHAN EKOSISTEM SEBAGAI SOLUSI KONFLIK DI TAMAN NASIONAL GUNUNG HALIMUN SALAK - Dadang Edi Rochaedi; Dolly Priatna; Sata Yoshida Srie Rahayu (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2021)
The ecosystem restoration conservation partnership program is a new policy from the Ministry of Environment and Forestry which aims to reduce conflicts due to forest land use in conservation areas. Gunung Halimun Salak National Park (GHSNP) is one of the conservation areas facing tenure conflicts, particularly in the Gunung Botol Resort area, where there are people who have lived and cultivated the land for decades, long before the Decree of the Designation of the GHSNP was issued. In an effort to address tenurial conflicts in Malasari Village, which is one of the villages within the management area of Gunung Botol Resort, the community took the initiative to collaborate with the GHSNP manager through a scheme called ecosystem restoration conservation partnership. This study aims to formulate a strategy for developing an ecosystem restoration conservation partnership in GHSNP by using a qualitative approach which is presented in a descriptive form. Data were analyzed using SWOT (Strengths, Weaknesses, Opportunities, and Threats) technique. The results of the study indicate that the ecosystem restoration conservation partnership program is recommended to be implemented by utilizing existing strengths and opportunities, as well as developed through synergy and collaboration that involves multi-stakeholders.